1997
DOI: 10.1038/36849
|View full text |Cite
|
Sign up to set email alerts
|

A role for the Ras signalling pathway in synaptic transmission and long-term memory

Abstract: Members of the Ras subfamily of small guanine-nucleotide-binding proteins are essential for controlling normal and malignant cell proliferation as well as cell differentiation. The neuronal-specific guanine-nucleotide-exchange factor, Ras-GRF/CDC25Mm, induces Ras signalling in response to Ca2+ influx and activation of G-protein-coupled receptors in vitro, suggesting that it plays a role in neurotransmission and plasticity in vivo. Here we report that mice lacking Ras-GRF are impaired in the process of memory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
241
2
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 441 publications
(262 citation statements)
references
References 30 publications
16
241
2
3
Order By: Relevance
“…A similar increase in the 42-kDa, but not 44-kDa, protein had been reported by English and Sweatt [121] after induction of long-term potentiation in hippocampal CA1. Thus it is difficult to reconcile that mutant mice lacking Ras-GRF, a small G-protein family member, did not show abnormalities in hippocampal synaptic plasticity or hippocampus-dependent learning [122]. However, longterm plasticity is abnormal in the amygdala, and longterm memory is reduced for contextual or cued conditioning.…”
Section: Mapk Cascadementioning
confidence: 94%
“…A similar increase in the 42-kDa, but not 44-kDa, protein had been reported by English and Sweatt [121] after induction of long-term potentiation in hippocampal CA1. Thus it is difficult to reconcile that mutant mice lacking Ras-GRF, a small G-protein family member, did not show abnormalities in hippocampal synaptic plasticity or hippocampus-dependent learning [122]. However, longterm plasticity is abnormal in the amygdala, and longterm memory is reduced for contextual or cued conditioning.…”
Section: Mapk Cascadementioning
confidence: 94%
“…Additional support of the involvement of Ras-dependent signalling came from another strain lacking the neuronal specific Ras exchange factor RasGRF. In contrast with NF1 mice, RasGRF −/− mice are viable and fertile and do not manifest gross morphological alterations in overall brain organisation [53]. Yet Ras-GRF KO mice are severely impaired in amygdala-dependent behavioural tasks, such as operant and classical conditioning tests.…”
Section: Genetic Experimentsmentioning
confidence: 98%
“…Consequently, further progress may be made by examining the role of imprinted genes in adult brain functions such as discrete aspects of cognition. This has been reviewed elsewhere (Isles & Wilkinson 2000), but in summary animal studies have so far demonstrated that imprinted genes impact on behavioural flexibility (Davies et al 2005a) and several different aspects of memory functioning, including emotional (Brambilla et al 1997), context dependent (Jiang et al 1998) and spatial (Muscatelli et al 2000). Studies on human mental dysfunction indicate a similar array of possible roles for imprinted genes in cognitive functioning (reviewed in Davies et al 2001), including behavioural flexibility (Skuse et al 1997), spatial memory (Curfs et al 1991) and mental rotation (Bishop et al 2000), and what can be broadly described as 'social cognition' (Cook et al 1997;Skuse et al 1997;Boer et al 2002).…”
Section: Sex-biased Dispersal Intragenomic Conflict and Social Behavmentioning
confidence: 99%